Completeness of colon and rectal cancer staging in the Danish Cancer Registry, 2004–2009 - Ostenfeld, Eva Bjerre (Dove Medical Press, 2012)
OBJECTIVE: To explore the completeness of tumor, node, metastasis (TNM) staging for colon and rectal cancer in the Danish Cancer Registry. MATERIAL AND METHODS: From the Danish Cancer Registry, we retrieved data on TNM stage, year of diagnosis, sex, and age for 15,976 and 8292 patients, respectively, with first diagnoses of colon or rectal cancer during the 2004–2009 period. From the Danish National Patient Register, we retrieved data on comorbidity (computed as Charlson Comorbidity Index scores). We calculated the completeness of TNM staging overall, by each stage component, and according to a stage algorithm allowing some missing stage components. Analyses were stratified by sex, age, year of diagnosis, and Charlson Comorbidity Index score. RESULTS: For colon and rectal cancer, overall TNM completeness was 67.8% (95% confidence interval [CI]: 67.0%–68.5%) and 68.1% (95% CI: 67.0%–69.1%), respectively. For both cancers, completeness decreased with increasing age and level of comorbidity, whereas differences between the sexes were minor. Over the study period, TNM completeness for colon cancer decreased from 71.3% (95% CI: 69.5%–73.0%) to 64.8% (95% CI: 63.0%–66.6%), whereas the completeness for rectal cancer remained stable over time. When using the stage algorithm, the completeness rose markedly, to 81.1% for colon cancer and 79.0% for rectal cancer. CONCLUSION: One-third of colon and rectal cancer cases in the Danish Cancer Registry had missing TNM stage information, which varied with age and level of comorbidity. Cancer cases with unknown staging warrant serious consideration of the methodological implications in future epidemiological studies monitoring cancer incidence and outcomes.